Relevansi dan Efektivitas Metode Resitasi Dalam Meningkatkan Prestasi Belajar Siswa - Ali, Muhammad Mahrus (Perkumpulan Alumni dan Santri Mahyajatul Qurro’, 2021)
This study aims to determine the relevance and effectiveness of implementing the recitation method in improving student achievement. This research is directed to answer two problems: the relevance and effectiveness of the recitation method in learning Akidah Akhlaq subjects. Classroom Action Research with a quantitative research approach is used in the research method where data collection uses research measuring instruments (instruments). Data analysis is quantitative/statistical, aiming to test and prove the hypotheses that have been made/set. The data analysis technique used in this study was carried out in several stages, namely: a) data reduction, b) data presentation and c) conclusion drawing, data analysis in research using SPSS (Product Moment). The recitation method was applied to the subjects of Aqidah Akhlak grade 5. The conclusions followed the study results with the acquisition of scores and percentages: Cognitive score acquisition in cycle-1: 85.88 in cycle-2: 87.06, which means up: 1.18. the acquisition of affective values ​​in cycle-1: 89.41 in cycle-2:89,26. It means down: 0.15. The group score in the first cycle: 86.47 in the second cycle 89.41. It means up: 0.99. The acquisition of psychomotor scores in cycle-1: 90.69 in cycle-2 90.69. It means fixed. The average score (average) in cycle-1: 88.11 in cycle-2: 89.11 means that the value increases by: 0.99. The research analysis results can be concluded that the recitation method in Akidah Akhlaq subjects is relevant and effective in improving student achievement.